Методична модель формування виконавської культури підлітків в процесі співацької діяльності - Стрюк Мирослава; Striuk Myroslava (Видавництво «Код», 2025)
Резюме. У статті здійснено аналіз наукової літератури з метою визначення методичної моделі виконавської культури підлітків в процесі співацької діяльності. Розглянуто відмінності та особливості дефініцій педагогічні принципи та педагогічні умови. Зважаючи на специфіку музичного мистецтва, була звернута увага на наступні педагогічні принципи: емоційної зацікавленості та емпатійності; інтеграції мистецьких знань; опори на художньо-естетичний досвід; орієнтації на художньо-естетичні потреби і смаки учнів; творчої свободи в художній інтерпретації вокального твору.

Abstract. The article analyzes the scientific literature with the aim of defining a methodological model of the performing culture of adolescents in the process of singing activities. It examines the differences and peculiarities of definitions, educational principles, and pedagogical conditions. Considering the specifics of musical art, attention was paid to the following principles: emotional engagement and empathy; integration of artistic knowledge; reliance on artistic-aesthetic experience; orientation towards the artistic-aesthetic needs and tastes of students; creative freedom in the artistic interpretation of vocal works. It is stated that pedagogical principles and conditions work in close interaction, comprehensively. Important pedagogical conditions noted are: creating a pleasant and creative atmosphere; maintaining a balance between educational and recreational functions in the educational process; actively involving students in concert practice; stimulating the practical implementation of musical and creative products in artistic works. Further research on the phenomenon of performing culture among adolescents in the process of singing activity is mentioned. Thus, we have considered the appropriate pedagogical principles and conditions for the formation of the performing culture of adolescents in the process of singing activity. The highlighted pedagogical principles and conditions are focused on the need to develop the emotional sphere of students, maintain a creative and friendly environment, maintain a balance of educational and entertainment functions in the educational process, activate students in concert practice and creative freedom in interpretative activity.
Methodological model of forming performing culture of teenagers in the process of singing activities
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-16?authuser=0
Keywords: виконавська культура; педагогічні принципи та умови; учні підліткового віку; співацька діяльність; музично-естетичний досвід; емоційна сфера